Spontaneous corneal perforation post cataract surgery. (13th December 2011) - Chaudhary, Rishika; Mushtaq, Bushra
Abstract : A 69-year-old female was referred for bilateral cataracts. Best-corrected visual acuity was 6/12 oculus dexter (OD) and 6/18 oculus sinister (OS). On examination, tear film breakup time was 8 s, signifying mild dry eyes; otherwise was unremarkable. The patient underwent uneventful left cataract surgery. At a 1 month postoperative examination vision was 6/9. The left cornea was dry with extensive punctuate epithelial erosions. There was no lagophthalmos. Lubricants were started to both eyes. The authors proceeded with right cataract surgery. Postoperative preservative free drops were given. She failed to attend an earlier than routine 2 week postoperative examination. Four weeks postoperatively, the vision was 2/60. She was incompliant with the lubricant drops. Biomicroscopic examination showed a sterile painless paracentral corneal perforation with iris plugging, Seidel's negative. She was started on steroid drops and lubricants. A lower lid punctual plug was inserted. The best corrected vision at 4 months was 6/18 OD and 6/6 OS.